PENYEBAB MISKONSEPSI PADA OPTIKA GEOMETRIS - Saputri, Dwi Fajar; Nurussaniah, Nurussaniah (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Misconception students on geometric optic concept are still found. The aim of this study to find out the cause of misconception students in understanding the concept of geometric optic in the Physics Education Program IKIP PGRI Pontianak. This study used an experimental method with descriptive analysis. The whole second semester 2014/2015 years students are population in this study. The research sample is determined using purposive sampling. Data obtained using doagnostic test with Certainty of Response Index (CRI) which is to determine the misconceptions profile. Furthermore, depth interview is used to determine the factors that cause misconceptions. The results showed that the cause of misconception students on geometric optic concept is preconception, intuition, associative thinking and humanistic, incomplete reasoning and the abilty of the student. Keywords: the cause of misconception students, geometric optic.